Linking glacier retreat with climate change on the Tibetan Plateau through satellite remote sensing - F. Zhao; F. Zhao; W. Gong; S. Bianchini; Z. Yang (The Cryosphere)
Under global climate change, glaciers on the Tibetan Plateau are experiencing severe retreat, which significantly impacts the regional water cycle and the occurrence of natural hazards. However, detailed insights into the spatiotemporal patterns of this retreat and its climatic drivers remain insufficiently explored. In this study, an adaptive glacier extraction index (AGEI) is proposed based on the analysis of multispectral Landsat images integrated with the Google Earth Engine, and comprehensive and high-resolution mapping of glaciers on the Tibetan Plateau is realized at 5-year intervals from 1988 to 2022. Subsequently, the ERA5-Land air temperature and precipitation data are downscaled to a finer 1 km resolution. Finally, the impacts of the annual and seasonal changes in the downscaled meteorological factors on the glacier extent are quantified. Results demonstrate a rapid yet heterogeneous pattern of glacier retreat across the Tibetan Plateau between 1988 and 2022, with retreat rates ranging from 0.14 ± 0.07 % to 0.51 ± 0.09 % annually. A notable trend is observed: most glaciers experienced a decrease in extent from 1990 to 2000 followed by a slight increase from 2000 to 2010. From 2010, a majority of the glaciers exhibited either a static state or minimal retreat. The most pronounced impact of annual temperature on glacier retreat is observed in the southern Himalayas, with a value of −9.34 × 103 km2 °C−1, and the most restraining impact of precipitation on glacier retreat reaches 261 km2 mm−1, which is observed in the Karakoram Range for the spring season. These insights are pivotal in comprehending the temporal and spatial heterogeneity of glacier retreats and in understanding the effects of climatic variations on the state of glaciers on the Tibetan Plateau.